Ocular Survey in Kathmandu University Medical Students - Shrestha, P.; Kaiti, R.; Shyangbo, R.; Dhakal, K. (Kathmandu University Medical Journal, 2022)
Background Medical students spend long time in academic activities that increases the risk of developing refractive errors and dry eyes that can affect their learning and social abilities. Only a few studies are available regarding ocular problems and its contribution to visual impairment among medical students in Nepal. Objective To evaluate the ocular problems among the medical students in a University hospital. Method An observational, descriptive, cross-sectional study was conducted among five batches undergraduate medical students until 2022 of Kathmandu University School of Medical Sciences, Dhulikhel, Kavre. A self-administered questionnaire was used to obtain demographic data and information on visual problems followed by a detailed ocular examination that included refraction, color vision and Schirmer test. Result Total of 284 medical students (with 568 eyes) with mean age of 22.8 years, 179 males and 105 females were enrolled. Among them, 270 (47.5%) eyes were emmetropic. Simple Myopia was the commonest followed by Compound Myopic Astigmatism. The mean spherical equivalent in right and left eye were -0.914 ± 1.54 and -0.886 ± 1.53 respectively. Approximately 18% students had some form of dry eye. Nineteen students (6.7%) had color vision deficiency and 13 (4.6%) had deuteranomalia, 3(1.1%) had deuteranopia and 3(1.1%) had protanomalia. Conclusion Eye defects, like refractive errors, dry eyes and color blindness, are common among medical students. They need to be advised for frequent eye check up in order to diagnose eye defects timely and arrest visual impairment at early stage.